The Effectiveness of Quizizz Application-Assisted Learning to Improve Student Self-Efficacy - Ekaputra, Firdiawan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study was to examine the effectiveness of learning assisted by the Quizizz application in improving students' self-efficacy. This study used a one-group pretest-posttest research design. The study was conducted on 23 students majoring in Chemistry Education in class R-001 in the Odd Semester of the 2025/2026 Academic Year. The data collection technique in this study was a questionnaire aimed at measuring self-efficacy before and after learning assisted by the Quizizz application. The data on students' self-efficacy abilities were then tested using a paired sample t-test. The conclusion of this study is that the application of the Quizizz application in learning is proven to be effective in increasing students' self-efficacy. This increase may be due to the Quizizz application having interesting and comprehensive features and providing quick feedback, making learning competitive and enjoyable and providing more flexible independent learning opportunities.